Preferences for Capturing Market Share of Halal Products in the 5.0 Era Through the UTAUT-3 Model for MSME in Lhokseumawe City - Safwan, Safwan; Maulana, Nora; Mulyani, Rita; Ismail, Ismail (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This study aimed to develop a new model for MSME growth and identify key factors influencing the increase in halal market share among MSME through empirical testing of the Unified Theory of Acceptance and Use of Technology (UTAUT-3). A mixed-method sequential explanatory approach was employed. The sample was selected using purposive sampling, resulting in 70 respondents. Quantitative data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, while qualitative data were examined through triangulation and the Analytical Network Process (ANP) method. The findings revealed that all independent variables—including performance expectancy, business expectancy, social influence, facilitating conditions, hedonic motivation, price value, habits, and personal innovation—had a significant positive effect on behavioral intentions to use QRIS among MSME actors in Lhokseumawe City. These results highlight the need for more intensive and comprehensive utilization of digital technology to achieve optimal business performance. The adoption of QRIS, strengthening of halal branding, product innovation, and increased competitiveness are strategic steps toward building partnerships with various stakeholders and developing a sustainable halal MSME ecosystem. Supportive government policies and programs are essential for fostering an ecosystem that promotes technology adoption and the growth of halal products in the 5.0 era.